Bahamas sets sights on LatAm with ICON : newly launched Investment Condominium is a perfect product to penetrate investment fund-driven Latin American markets - Allen, Aliya (2015)
Presents information on ICON defined as a contractual relationship subsisting between investors, under which the investors agree to pool assets for the purpose of investing those assets as a collective.